Copper-catalyzed cascade annulation between α-bromocarbonyls and biaryl or (Z)-arylvinylacetylenes enabling a direct synthesis of dibenzocycloheptanes and related compounds. Issue 97 (15th November 2016) - Lu, Danyang; Wan, Yimei; Kong, Lichun; Zhu, Gangguo
Abstract : Copper-catalyzed cascade annulation of γ, δ-unsaturated α-bromocarbonyls with biaryl or ( Z )-arylvinylacetylenes is presented, giving an expeditious access to dibenzocycloheptanes and related compounds in moderate to high yields. Abstract : Copper-catalyzed cascade annulation of γ, δ-unsaturated α-bromocarbonyls with biaryl or ( Z )-arylvinylacetylenes is presented, giving an expeditious access to dibenzocycloheptanes and related compounds in moderate to high yields. It provides a novel method for the one-pot synthesis of cycloheptane and cycloheptene-fused polycyclic scaffolds featuring a rare 7- endo-trig radical cyclization.